(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article presents the results of an experimental study of gender characteristics of men, how girls, who grew up and were brought up in incomplete paternal (maternal) families, consider them in the period of mature youth. The specificity of the attitude of girls from an incomplete family towards men is established. Attention is focused on classification of masculine, feminine and androgynous qualities of men in the views of respondents from incomplete and complete families. Analysis of the results of the study enabled to partially approach to the reasons for the formation of ideas about the amount of properties and characteristics objectively typical for men in their views on girls who were brought up in families without a father